Structural Properties of 2/2 Hemoglobins: The Group III Protein from Helicobacter hepaticus - Nothnagel, Henry J. (2011)
The ε-proteobacterium Helicobacter hepaticus (Hh) contains a gene coding for a hemoglobin (Hb). The protein belongs to the 2/2 Hb lineage and is representative of Group III, a set of Hbs about which little is known. An expression and purification procedure was developed for Hh Hb. Electronic absorption and NMR spectra were used to characterize ligation states of the ferric and ferrous protein. The pK(a) of the acid/alkaline transition of ferric Hh Hb was 7.3, an unusually low value. NMR analysis of the cyanomet complex showed the orientation of the heme group to be reversed compared to most Group I and II 2/2 Hbs. Ferrous Hh Hb formed a stable cyanide complex that yielded NMR spectra similar to those of the carbonmonoxy complex. All forms of Hh Hb self-associated at NMR concentrations. Comparison was made to the related Campylobacter jejuni 2/2 Hb (Ctb), and the amino acid conservation pattern of Group III was re-inspected to help in the generalization of structure–function relationships.